PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN TEKNIK PEMODELAN PADA SISWA SMKN 8 PONTIANAK - Pajariani, Wulan; Syambasril, Syambasril; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was based on student got low score of writing description text of  X grade student DKV 1 SMKN 8 Pontianak academic year 2016-2017. student get low score because learning activities is done in one direction. The teacher still used lecturing in the process of learning and was became monoton to us. Alternative to solve the problem is use modelling technique to improve students writing skill description text. The purpose of this research is to describe learning of writing description text through modelling technique to the X grade students DKV 1 SMKN 8 Pontianak academic year  2016-2017. The method of this research was desciptive, in form of qualitative. The research was classroom action research and done through 2 cycle. Data source of this reseach was the teacher of Bahasa Indonesia and student of X DKV 1 SMKN 8 Pontianak. The data was taken through observation and test. After the implementation of modelling technique score of writing description text was increased from mean score 71 in first cycle to 75 in second cycle. The result of this research showed applying the effective method can fixed the problems and can increase the student’s achievement in teaching learning process in classroom.Keywords: Modelling Tecnique, Description Text, Writing.